Isolation and characterization of neural stem cells from buffalo. (1st June 2014) - Kumar, Kuldeep; Singh, Renu; Kumar, Manish; Agarwal, Pranjali; Mahapatra, P S; Kumar, Ajay; Malakar, Dhruba; Bag, Sadhan
Abstract : Neural stem cells (NSCs) are primordial, uncommitted cells postulated to give rise to the array of more specialized cells of the central nervous system (CNS). NSCs can self-renew and give rise to neurons, astrocytes and oligodendrocytes. NSCs are found in the CNS of mammalian organisms, and represent a promising resource for both fundamental research and CNS repair. Animal models of CNS damage have highlighted the potential benefit of NSC-based approaches. Present study described that buffalo neural stem cells (Bu-NSCs) were isolated and expanded rapidly from buffalo fetal brain in adherent culture. They were capable of multidifferentiation into neurons, astrocytes, and oligodendrocytes. Bu-NSCs were morphologically homogeneous and possessed high proliferation ability. The population doubled every 128.16 h. Normal buffalo karyotype was unchanged throughout the in vitro culture period. Together, we have isolated and cultured Bu-NSC from fetal brain that showed self-renewal, rapid proliferation and ability to differentiate into cells of nervous system. The availability of such cells may hold great interest for basic and applied neuroscience.